Presupposing Legal Authority. (25th October 2021) - Mullins, Robert
Abstract: The thesis that law necessarily claims authority is popular amongst legal philosophers. Some distinguished legal philosophers, including the late John Gardner, Joseph Raz and Scott Shapiro, have suggested that support for this thesis is found in legal officials' use of deontic language. This article begins by considering the merits of this suggestion. I discuss two unpromising arguments for the claim thesis based on the use of deontic language in law. I then suggest that a more plausible basis for the claim thesis lies in the felicity conditions of the speech acts that legal officials perform. In the absence of an explicit claim to authority, legal officials make a presupposition to authority over their subjects. The presupposition arises from interaction between the felicity conditions of legal speech acts and basic norms of cooperative communication. I consider some implications of this conclusion for our understanding of legal authority.